Current short-term career aspirations of dental students in Malaysia: post new employment policy = Malezya’daki diş hekimliği oğrencilerinin kısa dönem kariyer hedefleri: yeni İstihdam politikası sonrası - Che Musa, Muhd Firdaus; Mustapa, Anis Zafirah; Roslan, A'isyah; Abu Kasim, Azyan (DergiPark Akademik, 2020)
OBJECTIVE: It is important to revisit career aspirations of emerging dental graduates following the dynamic changes in employment policies in Malaysia for workforce stability. The aims of this study were to explore current students’ short career aspirations and their perceived influences, and whether their aspirations vary according to students’ characteristics. METHODS: All final year dental students who registered in 2017/2018 academic year (n=64) in International Islamic University of Malaysia (IIUM) were invited to participate in a self-administered questionnaire. The instrument explored the students’ motivation, short and long-term career aspirations and influences using mixture of open and close ended questions. Data were analysed using SPSS programme, including Chi-Squared test for linear association. RESULTS: The response rate was very high (n=62; 97%). The majority were aged 25 years (63%), female (71%), and come from high-income families (38%). All of the participants were Malaysian. In regard to their short-term aspiration, the participants mostly chose ‘gain knowledge/skill/experience’ (39%); followed by ‘undertaking specialist training’ (27%) and ‘getting a permanent job’ (20%). ‘Achieving financial stability’ (80.6%), ‘gaining professional experience’ (80.6%), and ‘balance of work-life’ (73%) were their greatest influences. Notably, there were significant differences between ‘having a break from study’ (p=0.030) and choosing area of practice (p=0.017) by family income. Furthermore, male students were anticipated to work in private sector more than their female counterpart (p=0.030). CONCLUSION: There is a transient with the most significant short-term career aspirations post new employment policy among Malaysian dental students to study dentistry. Enhancement of knowledge, skills and experiences was observed the greatest amongst all respondent; in securing financial and professional stability; as well as work-life balance. The students’ short-term career aspirations varied based on the students’ family income and gender.